EVALUATING NEUROLOGY CME IN TWO EDUCATIONAL METHODS USING PATTON’S UTILIZATION FOCUSED MODEL - Vakani, Farhan; Ahmad, Amina; Sonawalla, Aziz; Sheerani, Mughis (Journal of Ayub Medical College Abbottabad, 2013)
Background: Generally in continuing education medical education (CME) the most time is consumed for in the planning and preparation of the event. This planning and preparation, however, needs recognition through an evaluative process. The purpose of this study was to evaluate neurology CME in two educational methods, lecture vs task-based learning, using Patton’s utilisation focused model. Methods: This was an observational, cross-sectional inquiry. The questionnaire evaluated the educational elements such as learning objectives met, content covered, presentations at the level of understanding, level of interaction, knowledge gained, time management, queries responded, organisation, quality of learning material and overall grading of the educational event. General Practitioners were the key participants in this evaluation and consisted of 60 self-selected physicians distributed equally in both the TBL and lecture groups. Patton’s utilization focused model was used to produce findings for effective decision making. The data were analysed using Mann-Whitney U test to know the value of the learning method that satisfied the most participants. Results: A total of 58 evaluations were returned, 29 from the TBL group and 29 from the lecture. The analysis of the elements showed higher mean ranks for TBL method ranging between 32.2 and 38.4 versus lecture (20.6-26.8). Most of the elements assessed were statistically significant (p>0.05), except time management (p=0.22). However, elements as ’˜objectives of the activity met’ (p=0.07), ’˜overall grading of the event’ (p=0.06) and ’˜presentations at the level of understanding’ (p=0.06) were at border line. Of the 29 respondents in the TBL group, 75% rated all the elements of the program above very good. In the lecture group, 22 (75%) respondents out of 29 rated almost half of the elements above very good. Conclusion: Majority of respondents in the TBL group rated all program elements as exceptional compared to the lecture group in which only half of the elements were rated above very good. Task-based learning method made the most impact on participants’ satisfaction. Keywords: Evaluation, Management-oriented, Task-based learning, Lecture